Caplacizumab for immune thrombotic thrombocytopenic purpura: real-world multicenter data - Gavriilaki, Eleni; Nikolousis, Emmanuel; Koravou, Eudoxia-Evaggelia; Dimou-Besikli, Sotiria; Kartsios, Charalampos; Papakonstantinou, Anna; Mpanti, Anastasia; Pontikoglou, Charalampos; Kalpadaki, Christina; Bitsani, Aikaterini; Tassi, Ilianna; Touloumenidou, Tasoula; et al. (Frontiers in Medicine, 2023)
Given the limited real-world data of caplacizumab, our multicenter real-world study was designed to assess the safety and efficacy of caplacizumab in immune thrombotic thrombocytopenic pupura (iTTP), compared to historic controls. We have studied 70 patients: 23 in the caplacizumab and 47 in the historic control group. Plasma exchange was applied in all episodes except for two patients that denied plasma exchange. Rituximab as first-line treatment was more common in the caplacizumab group compared to historic control. Caplacizumab (10 mg daily) was given at a median on day 7 (1–43) from initial diagnosis for 32 (6–47) dosages. In the caplacizumab group, a median of 12 (8–23) patients required plasma exchange sessions versus 14 (6–32) in the control group. Caplacizumab administration did not produce any grade 3 complications or major hemorrhagic events. After a median of 19.0 (2.6–320) months since the iTTP diagnosis, 5 deaths occurred (4 in the control group and 1 in the caplacizumab group, p = 0.310). Caplacizumab patients achieved early platelet normalization and ADAMTS13 activity normalization at the end of treatment. Relapse was observed only in 2/23 (9%) caplacizumab patients, compared to 29/47 (62%) historic controls (p < 0.001). Overall, caplacizumab is safe and effective in treating iTTP, including cases refractory to plasma exchange, re-administration, and cases without previous plasma exchange treatment. No major hemorrhagic events were observed. Cessation of dosing guided by ADAMTS13 has ensured a low relapse rate.